2008
DOI: 10.1088/1748-6041/3/2/025011
|View full text |Cite
|
Sign up to set email alerts
|

The biocompatibility of SLA-treated titanium implants

Abstract: The titanium implant surface was sandblasted with large grits and acid etched (SLA) to increase the implant surface for osseointegration. The topography of the titanium surface was investigated with scanning electron microscopy (SEM) and a profilometer. The SLA implant demonstrated uniform small micro pits (1-2 microm in diameter). The values of average roughness (R(a)) and maximum height (R(t)) were 1.19 microm and 10.53 microm respectively after sandblasting and the acid-etching treatment. In the cell-surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 23 publications
2
91
0
2
Order By: Relevance
“…64 The effect of grain refinement of the bulk of the material on the surface characteristics, which in turn control fatigue properties and cellular response, may be weakened by such surface treatments. A recent study 60 shed some light on the effect of sand-blasting combined with acid-etching (the SLA process 65 ) on the fatigue performance of CP Ti. The study demonstrated that the SLA surface treatment of Ti with different bulk microstructures gave rise to different levels of surface roughness.…”
Section: Nanostructured Biomaterialsmentioning
confidence: 99%
“…64 The effect of grain refinement of the bulk of the material on the surface characteristics, which in turn control fatigue properties and cellular response, may be weakened by such surface treatments. A recent study 60 shed some light on the effect of sand-blasting combined with acid-etching (the SLA process 65 ) on the fatigue performance of CP Ti. The study demonstrated that the SLA surface treatment of Ti with different bulk microstructures gave rise to different levels of surface roughness.…”
Section: Nanostructured Biomaterialsmentioning
confidence: 99%
“…Microspheres of diameter in the range 10-540 µm are typically accelerated toward the surface to be treated, using a compressed air or nitrogen blow. Most used grid materials include corundum (Al 2 O 3 ) [9,10], silicon carbide (SiC) [11], titania (TiO 2 ) [12], hydroxyapatite (HA) [13], zirconia (ZrO 2 ) [14], silica (SiO 2 ) [15] and aluminum powders [15]. The main effect of sandblasting is to change the morphology of the treated surface, substantially increasing its roughness.…”
Section: Surface Treatmentsmentioning
confidence: 99%
“…The main effect of these acid-etching processes is to modify the implant morphology by producing micro-pits of a few microns diameter on titanium surfaces [16,17]. These processes are commonly applied after sandblasting, and the complete process, usually referred to as sandblasting and large grit acid etching (SLA) [18], is often considered the reference surface treatment to which other ones are compared [12,[16][17][18]. The most common process involves the use of Al 2 O 3 microspheres of 200-540 µm diameter, followed the etching with a mixture of HCl and H 2 SO 4 [16].…”
Section: Surface Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os implantes de superfície tratada com ataque ácido e jateamento de areia ou "sandblasted and acid-etched" (SAE) combinam jateamento com partículas de alumina e condicionamento ácido para obter macro-rugosidade e microporos (Kim et al, 2008). A superfície tratada por oxidação anódica ou "anodic oxidation" (AO) é resultante de um processo eletroquímico que aumenta a superfície da camada de óxido de titânio e de rugosidade (Aalam;Nowzari, 2005).…”
Section: Introductionunclassified